Pengaruh Lingkungan Kerja, Disiplin Kerja, Dan Motivasi Kerja Terhadap Kinerja Individu Karyawan Ninja Xpress Tebo (MRB-TBO) Kabupaten Tebo Provinsi Jambi - Wijaya, Ridho (Universitas Muhammadiyah Metro, 2023)
This study aims to examine the effects of Work Environment, Work Discipline and Work Motivation on Employee Performance in Ninja Xpress Tebo (MRB-TBO) Tebo Regency, Jambi Province. This study uses a probability sampling method that is saturated sampling where all members of the population are sampled. The sample in this study were all employees of the Ninja Xpress Tebo (MRB-TBO) Tebo Regency, Jambi Province. Data were collected by questionnaires. Techniques analyzed using SPSS version 25 including validity test, reliability test, descriptive statistics, classic assumption test, multiple linear regression test, hypothesis test and coefficient of determination. The results of study state that Work Environment do not effect on employee performance. While work environment and work motivation variables have a positive and significant effect on employee performance.